Konsep Pemasaran Berbasis Aida Terhadap Peningkatan Pendapatan Pembiayaan Di “Villa Hidden Space”, Desa Lemukih, Kecamatan Sawan, Kabupaten Buelleng - Ni Kadek Ayu Trisnadewi; I Putu Gede Parma; I Putu Agus Adnyana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
One marketing strategy that can be done so that a company continues to have excellence is the communication strategy marketing. Communication strategies responded to consumers to be stimuli. One form of response to marketing communication stimuli is through the concept of AIDA (Attention, Interest, Desire, Action). AIDA model (Attention, Interest, Desire, Action) is one of the response hierarchy models that is quite popular for marketers as a guide in carrying out marketing activities. The purpose of this study was to determine the decision-making process of consumers staying at Villa Hidden Space. The data analysis technique used is the validity and reliability test as well as the descriptive qualitative analysis. This study is intended to determine the relationship between AIDA and increase in sales revenue at Villa Hidden Space. In this study there are 5 (five) hypotheses. Respondents in this study were 50 respondents, guests who stayed at Villa Hidden Space. Then an analysis of the data obtained using multiple regression using SPSS. In this study the results obtained are changes that are increase in sales revenue influenced by AIDA (Attetion, Interest, Desire, Action by 84.5% and the remaining 15.5% is influenced by other variables not examined in this study. Keywords: AIDA and Increasing Financing Income